Design of noise Control Scheme for 500kV Substation. Issue 4 (February 2020) - Hu, Sheng; Chen, Wei; Wu, Xiaowen; Xie, Yine; Tang, Qi; Lu, Ling
Abstract: The noise of substation is generally generated by the main transformer, reactor, capacitor and other electrical equipment, in which the transformer is the main sound source equipment. Its spectrum characteristics are mainly low frequency noise, medium and high frequency noise as auxiliary. The noise band is wide, the wave grow is long, the attenuation is slow, and the penetration ability to the building structure is strong, which seriously affects the daily life of the residents. In this paper, the noise source of a 500kV substation with noise exceeding the standard is tested and analyzed first, then the noise reduction scheme design and sound field simulation calculation are carried out to verify the feasibility of the scheme.